Three-dimensional fit of CAD/CAM-made zirconia copings - Moldovan, Ovidiu; Luthardt, Ralph G.; Corcodel, Nicoleta; Rudolph, Heike (Dental materials, 2011)
Objectives - CAD/CAM-technologies aim for a standardized, accurate production of dental restorations out of high strength materials (zirconia). The three-dimensional internal fit of CAD/CAM-manufactured zirconia copings was evaluated in vitro to verify the realizability of this aim. - Methods - The analysis was based on ceramic master dies of prepared teeth and corresponding virtual CAD surfaces. Five copings per die were manufactured with two different CAD/CAM-technologies: milling and grinding. The internal fit was determined by a three-dimensional replica technique by optical digitization and computer-assisted analysis. - Results - Mean internal gaps were 134/84μm (SD 78/28) for molar and 93/69μm (SD 56/35) for premolar copings (milling/grinding) using a digitizable silicone for the replicas representing the cement space; they were statistically significant regarding tooth and CAD/CAM-system (p<0.001). - Significance - All zirconia copings showed an internal accuracy of fit where the gap widths ranged within the current clinical recommendations. However, there still is room for improvement and further standardization of CAD/CAM-technologies.
Gesehen am 01.09.2022